2012
DOI: 10.1063/1.3682103
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the interlayer exchange coupling between single perpendicularly magnetized CoFeB layers

Abstract: We experimentally study the tunability of the Ruderman-Kittel-Kasuya-Yosida (RKKY) interlayer exchange coupling (IEC) in Pt/CoFeB/Pt/Ru/Pt/CoFeB/Pt stacks with perpendicular magnetic anisotropy (PMA). The perpendicular magnetization of a single Pt/Co60Fe20B20/Pt (at. %) shows full remanence and square hysteresis loops for a CoFeB thickness range of 0.60–1.0 nm. By inserting a Pt layer between the Ru and CoFeB, the PMA of the ultrathin CoFeB layers is stabilized and the IEC can be tuned. In particular, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…24 The switch to full magnetization occurs abruptly at a field which can be controlled by tuning the interlayer exchange coupling between the CoFeB layers via the Pt layer thickness on either side of the Ru layer. 25 This effectively tunes the width of the low field antiparallel region; the higher the antiferromagnetic RKKY coupling, the higher the H SW . The SAF is also characterized by high out of plane anisotropy, and hence an easy axis of magnetization.…”
mentioning
confidence: 99%
“…24 The switch to full magnetization occurs abruptly at a field which can be controlled by tuning the interlayer exchange coupling between the CoFeB layers via the Pt layer thickness on either side of the Ru layer. 25 This effectively tunes the width of the low field antiparallel region; the higher the antiferromagnetic RKKY coupling, the higher the H SW . The SAF is also characterized by high out of plane anisotropy, and hence an easy axis of magnetization.…”
mentioning
confidence: 99%
“…Subsequently, the IEC was also demonstrated in the magnetic systems with perpendicular magnetic anisotropy (PMA), in which the magnetic orientations of magnetic layers lie normal to the film plane. 5 However, till date a very few studies have focused on the systems with adjacent magnetic layers having magnetization perpendicular to each other. Along these lines, we herein propose a system consisting of ordered-CoPt hard layer having strong PMA and a Ni-Fe soft layer with IMA for understanding the effects of IEC as a function of thickness of spacers such as Ru and Pt.…”
mentioning
confidence: 99%
“…Another reason can be a well-developed layered structure with atomically flat interfaces of the present stacks, which was observed in high-resolution transmission electron microscopy experiments (results not shown). Recently, Choi et al 14 and Lavrijsen et al 15 reported that the ferromagnetic coupling observed in the very low t Ru range (t Ru < 0.6 nm) could be due to the roughness of the Ru spacer layer, possibly leading to the formation of ferromagnetic bridges.…”
mentioning
confidence: 99%